Aquisição da linguagem oral em crianças com a Síndrome congênita do Zika vírus. - Rapozo, Janiely Tinôco (2019)
This dissertation is a contemporary study, with few publications, regarding the process of oral language acquisition in children with Congenital Zika Virus Syndrome (SCZV). A major epidemic of this virus occurred in Brazil in 2015, associated with microcephaly, which was considered a worldwide public health problem. The study aimed to investigate how the process of oral language acquisition occurs in children with Congenital Zika Virus Syndrome. The research is based on Vygostky's social interactionism, and on other authors who deal with language acquisition such as Bruner, Piaget, Wallon. Moreover, among other authors, Eickman and Ventura was also used in the present study so as to comment on Zika Virus. The methodological path was guided by a qualitative and quantitative research. The research participants were ten (10) children with SCZV. They were treated at the Altino Ventura Specialized Rehabilitation Center, which is a reference center in Pernambuco. These children are roughly three (3) years old and in the period of oral language acquisition. They were followed for a period of nine (9) months. Two applications of the Developmental Screening Test scale (DENVER II) and the Behavioral Observation Protocol (PROC) were performed at the beginning and at the end of the intervention. The results of the DENVER II scale showed possible developmental delays in the four areas analyzed (social personnel, fine adaptive motor, language and gross motor). However, in PROC, 40% of the participants presented oral language acquisition in the form of simple sentences with two or three words; 30% isolated words and the remaining 30%, multimodal communication by gestures, facial expressions and vocalizations.The results of the research showed that the oral language stimulation employed in the treatment allowed the evolution of some of these children at the end of their follow-up period. Some have expanded their communication to words, simple sentences, and others employed various forms of verbal or nonverbal communication. Although these are the first studies, we were able to help clarify the oral language acquisition process of this group of children affected by SCZC. Furthermore, the stimulation was considered to be positive. As a result, it provoked in the children the desire to interact with the people around them, contributing to the improvement of the activities that may be proposed for them and to the process of school inclusion.